The need for an inflation buffer in the ECB's price stability objective: The role of nominal rigidities and inflation differentials - Agostino Consolo; Gerrit Koester; Christiane Nickel; Mario Porqueddu; Frank Smets (European Central Bank (ECB), 2021)
The existence of nominal rigidities and inflation differentials between countries offers two of the main rationales for an inflation buffer in a monetary union where monetary policy is oriented towards an area-wide inflation objective. Evidence accumulated since 2003 suggests that nominal rigidities remain a prevalent feature of the euro area, with some differences as regards prices and wages. Price setting may have become more flexible and there is no evidence for any especially strong downward rigidities in price setting. At the same time, persistent downward nominal wage rigidity (DWR) provides a strong argument for a positive inflation buffer to 'grease the wheels' of the euro area economy - also in order to avoid the risk of macroeconomic adjustments being managed in terms of quantities (unemployment) rather than prices when DWR is binding and particularly when productivity growth is low. Inflation differentials across euro area countries have tended to be small but persistent. For inflation dispersion in the euro area, the across countries has been more important than across regions, confirming that an inflation buffer might be especially important in a monetary union of different countries. Overall, inflation differentials were due to the rise of economic and financial imbalances in the first decade of the euro and the subsequent need for adjustment. Balassa-Samuelson effects which were highlighted in the 2003 strategy review were only a minor factor. By and large, the ECB's inflation objective seems to have provided a sufficient margin to prevent countries from having to live with prolonged periods of excessively low inflation rates in the period 1999-2019. There were some exceptions in the second decade of the euro (from 2009-2019), when inflation in the euro area was, overall, substantially lower than during the first decade.
Keywords: E31; E52; E24; 330; Monetary policy strategy review; HICP inflation; nominal rigidities; inflation differentials